Kinh doanh ngân hàng ngầm, hiệu quả và rủi ro: Bằng chứng thực nghiệm tại Việt Nam - Đinh Thị Thu , Hồng; Nguyễn Hữu , Tuấn; Trần Thị Hải , Lý (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This paper examines the impact of shadow banking on the commercial banks’ performance and risk using a sample of 30 domestic commercial banks in Vietnam in the period of 2005–2020. The research results show that with the measure of total income from all shadow banking services, or by the deduction approach, the profitability of domestic commercial banks increases when shadow banking activities increase. The deduction approach also shows that an increase in the size of shadow assets contributes to an increase in credit risk. For the estimation of shadow banking through the scale of non-bank financial institutions, the size of financing and leasing companies compared to total assets of banks have a positive effect on profitability of commercial banks, while the loan proportions of securities companies reduce bank performance.